2002
DOI: 10.1080/j003v14n02_07
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Serial Casting on Spasticity: A Literature Review

Abstract: This article is a literature review of the research regarding the use of serial casting in the treatment of spasticity. Spasticity has serious consequences, which impact activities of daily living and the quality of life. Classical studies in physiology indicate that muscle tissue immobilized in the shortened position can be physiologically changed through prolonged stretch. Serial casting has proven effective in improving such factors as range of motion and clinical measures of spasticity in spastic limbs. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The stretching exercises can cause discomfort to the children, they are time consuming for the patient their families (Hadden and Von Baeyer, 2002) and the physiotherapists (Wiart et al, 2008). Additionally, there is limited evidence to support functional improvements, e.g., in gait and mobility, after stretching interventions (Preissner, 2002;Katalinic et al, 2011;Harvey et al, 2017). Clearly a significant gap exists between the clinical rationale for implementing stretching and the supporting evidence for its intended effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The stretching exercises can cause discomfort to the children, they are time consuming for the patient their families (Hadden and Von Baeyer, 2002) and the physiotherapists (Wiart et al, 2008). Additionally, there is limited evidence to support functional improvements, e.g., in gait and mobility, after stretching interventions (Preissner, 2002;Katalinic et al, 2011;Harvey et al, 2017). Clearly a significant gap exists between the clinical rationale for implementing stretching and the supporting evidence for its intended effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…One strategy is to combine BoNT injection with therapeutic physical modalities [46]. Physical modalities have been shown to be effective in reducing hypertonia and increasing range of motion, such as splinting and casting [47][48][49][50][51]. However, a systematic review on the use of upper extremity casting found high variability in casting protocols which indicates no consensus in technique [52].…”
Section: Discussionmentioning
confidence: 99%
“…Casting, defined as a nonremovable external device, provides total contact pressure that provides prolonged muscle-tendon stretch for contracture prevention and may reduce the afferent sensory input from cutaneous, muscle, and joint receptors that contribute to spasticity. Casting may also contribute to a decreased alpha motor excitability which may also improve spasticity 9 …”
mentioning
confidence: 99%
“…Casting may also contribute to a decreased alpha motor excitability which may also improve spasticity. 9 A large observational study found that BoNT has a clinically significant effect on elbow flexor spasticity, a common pattern seen in poststroke patients. 10 Furthermore, a prospective study and a recent systematic review support that BoNT injection of the spastic upper limb muscles improves gait, which may be augmented by casting.…”
mentioning
confidence: 99%